Supply Chain Pattern and Value Added of Small-Scale Agribusiness Based on Pineapple in Punggur Sub-District - Sutarni Sutarni; Fitriani Fitriani; Bina Unteawati (Jurnal Penelitian Pertanian Terapan, 2021)
The purpose of this study was to analyze the distribution pattern of the people's scale pineapple commodity supply chain in Punggur District, calculate the marketing margin in the supply chain for community scale pineapple commodities in Punggur District, and analyze the value added of agro-industry. pineapple on the people's scale in Punggur District. The sampling method was simple random sampling. The number of samples for pineapple farmers was taken as many as 39 people and traders involved in pineapple supply chain channels, pineapple agro-industry players and end consumers. The method used to take samples of traders and end consumers with the snowball method is to follow the flow of the pineapple commodity supply chain from producers to consumers. The research method used is descriptive qualitative and quantitative approaches. The added value of the pineapple agro-industry was analyzed using the calculation of the added value of hayami. The results showed that the pineapple supply chain actors in the research area included; farmers, traders, retailers, and pineapple agro-industry. Farmers as pineapple cultivators are the primary members of the people's scale pineapple supply chain. The target market for people's scale pineapple products is the domestic market, namely markets inside and outside the province of Lampung. The distribution pattern of the dominant pineapple supply chain through intermediaries consists of 3 patterns. The products sold have 3 standards, namely grade A, Grade B, and Grade C. The marketing margin of fresh pineapple agribusiness between farmers and collectors is 26.51%. The pineapple lunkhead agroindustry provides added value of 63.98% Key words: pineapple, added value, margin, supply chain